LEGALITAS KIAI SEBAGAI WALI DALAM PERKAWINAN TANPA WALI NASAB - Muhammad Sirojudin Sidiq (LPPM STAI DARUSSALAM LAMPUNG, 2015)
Kiai as a guardian in marriage is a phenomenon that is not uncommonamong Islamic societies, especially in rural communities that tend tostudy Islamic law through the books of fiqih salaf, which until now stillcause pro-cons among the kiai / Scholars and other Islamic societies.The issue discussed in this paper is the argument of the legality of kiaias a guardian in marriage without the guardian of Islam accordingto Islamic law and the legislation in Indonesia, in order to explain thekiai's argument as a guardian in marriage, to explain the legal basisarising from the kiai as the guardian in Marriage under Islamic lawand legislation.The results of this study indicate that the kiai's law as a guardian inmarriage without guardian nasab, marriage is considered unlawfulaccording to laws and regulations applicable in Indonesia andillegitimate according to jumhur ulama, because the guardians whoshould carry out are the judges and not the kiai